PENGARUH OPERATING CAPACITY, STRUKTUR MODAL, DAN UKURAN PERUSAHAAN TERHADAP FINANCIAL DISTRESS - Afridayani Afridayani (Jurnal Aplikasi Akuntansi, 2023)
This study aims to examine the impact of operating capacity, capital structure, and firm size on financial distress. The type of research used is number-based and quantitative research. The data used comes from secondary sources. The population of this study consists of companies in the cyclical consumption sector that are listed on the IDX in the 2017-2021 period. The sample in this study was determined using a purposive sampling method, with a total of 16 companies that were observed for 5 years. Data analysis was carried out using Eviews software version 9. The results showed that operating capacity, capital structure, and firm size had an effect on financial distress. Operating capacity and firm size partially have an effect on financial distress, while capital structure does not partially affect financial distress.